POTENSI PENDIDIK DALAM MEMENUHI EKONOMI - Fati’ah Kusmaduni (JOEL: Journal of Educational and Language Research, 2022)
The profession of teachers or educators is a noble profession. However, to be able to perform the profession properly a teacher must meet the four competencies that have been required. A teacher who is able to meet these four competencies is a professional and certified teacher. Implementation of certification will of course affect teachers. Increasing prosperity in the form of fulfillment of economic needs as financial needs have been met is a direct impact of certification. In addition, teachers also have the potential to improve their economies by establishing entrepreneurship or self-employment.